STUDI ISOLASI DAN ESTERIFIKASI PATCHOULI ALKOHOL DARI MINYAK NILAM - , Ika Yuliawati ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Isolation and esterification of patchouli alcohol (PA) from patchouli oil has been conducted. Patchouli alcohol is the major constituent of patchouli oil. The first step of research, patchouli oil was separated into three fractions using fractional distillation under reduced pressure. Patchouli alcohol was crystallized from fraction III (containing 78.91% PA) using seeding method. Fraction III (108-116 oC) was cooled at -22 oC for 12 days. Crystal patchouli alcohol was determined its melting point (MP) and was characterized 1H-NMR. Patchouli acetate was synthesized by esterification of patchouli alcohol, acetic acid and H2SO4 catalyst at 50-52 oC for 3 h and sonication for 1, 2 and 3 h. Patchouli alcohol crystal obtained was 55.88% with >99% purity. The melting point of crystal was 52.10-55.70 oC. The 1H-NMR spectra data were ï¤ 1.94-1.77 (3H, m), 1.70-1.66 (1H, m), 1.48-1.20 (7H, m), 1.15 (1H, s, OH), 1.04 (6H, d, J 5.15 Hz), 0.81 (1H, s, tert-CH3), 0.76 (3H, d, J 7.17 Hz, sec-CH3). Patchouli acetate by esterification patchouli alcohol at 50-52 oC for 3 h is 53.58% and sonication for 1, 2 and 3 h is 17.92